Media framing of minorities’ crisis: a study on Aljazeera and BBC news coverage of the Rohingya - Kanaker, Osama; Abughazlih, Mohamed Oklah; Mohd Faizal Kasmani (Penerbit Universiti Kebangsaan Malaysia, 2020)
News nowadays is framed according to its makers. A single news item can be presented in different frames. The Rohingya are currently considered one of the most oppressed minorities worldwide. However, this minority did not receive enough support to alleviate their crisis. In this article framing theory is implemented to discover the frames used by Aljazeera and BBC in framing the causes and ramifications of the Rohingya crisis. This paper found out that news covered six main causes of the Rohingya crisis. The prominent cause that both Aljazeera and BBC agreed upon was security and military causes. 91.8% of the coverage was allocated to this prominent cause. The remaining 8.2% was for the other causes. Concerning ramifications, it was found out that news of Aljazeera and BBC collectively covered 20 ramifications. The majority of the ramifications were covered by both Aljazeera and BBC. However, Aljazeera independently cover 17 ramifications and the BBC independently covered only 10 ramifications. The main three ramifications that framed both Aljazeera and BBC news were deportation, mass massacres and oppression. Throughout the news observation, both Aljazeera and BBC framed their news by focusing on detailed incidents rather than establishing a holistic picture of the crisis. The frames implemented by Aljazeera and BBC were mainly the powerlessness frame and marginally the responsibility frame.